Integrative Bioinformatics Analysis Reveals Possible Target and Mechanism of Ellipticine Against Breast Cancer Stem Cells. - Adam Hermawan; Herwandhani Putri (Universitas Gadjah Mada, 2021)
Ellipticine (5,11-dimethyl-6H-pyrido[4,3-b]carbazole), an alkaloid isolated from plants Ochrosia elliptica, showed anticancer activity. A previous study demonstrated that ellipticine exhibited a reduction of the proliferation and self-renewal ability of ALDH1A1-positive breast cancer stem cells; however, the mechanisms have not been fully clarified. In this study, we aimed to identify the potential target and mechanism of ellipticine in breast cancer stem cells with a bioinformatics approach. Gene expression profiles predicting sensitivity and resistance of tumor cells to ellipticine were determined by microarray-based mRNA expressions from COMPARE. Gene list related to breast cancer stem cells was obtained from Pubmed with keywords "breast cancer stem cells". Protein-protein interaction (PPI) network construction, Gene Ontology (GO) and KEGG pathway enrichment analysis were carried out by STRING-DB. The genetic alterations of hub genes were analysed using cBioPortal. The prognostic value of the genes was evaluated using Kaplan-Meier survival curves. A Venn diagram of COMPARE microarray data and the gene list from PubMed generates two genes that are regulated by ellipticine and are related to breast cancer stem cells, namely XRCC5 and CD59. Ellipticine might target complement cascade and DNA repair mechanism in breast cancer stem cells. Ellipticine might target complement cascade and DNA repair mechanism in breast cancer stem cells. More importantly, CD59 is a potential biomarker to evaluate ellipticine bioactivity in BCSCs. Results of this study could be useful for elucidation of ellipticine molecular mechanism as well as for targeting BCSCs.